1997
DOI: 10.1007/bf02477692
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-ceria catalysts: Metal-support interactions and reactivity of palladium in selective hydrogenation of but-1-yne

Abstract: The influence of palladium-ceria interactions on the reactivity of palladium in but-1-yae hydrogenation has been investigated and compared with previous results obtained on alumina. The main differences from Pd-alnmina catalysts are (i) the enhancement of the turnover frequency ascribed to electron transfer from ceria to Pd, (ii) the diminution of the selectivity to but-l-ene, atm'buted to hydrogen spiUover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Thus, Additionally, it is known that both ceria-and lanthana-supported catalysts exhibit metal f support hydrogen spillover effects even at room temperature. [20][21][22] One may therefore speculate that scavenging of hydrogen from the gold by the support acts to promote the above two reactions, but not the homocoupling of iodobenzene to produce biphenyl, in accord with observation.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Thus, Additionally, it is known that both ceria-and lanthana-supported catalysts exhibit metal f support hydrogen spillover effects even at room temperature. [20][21][22] One may therefore speculate that scavenging of hydrogen from the gold by the support acts to promote the above two reactions, but not the homocoupling of iodobenzene to produce biphenyl, in accord with observation.…”
supporting
confidence: 58%
“…[20][21][22] One may therefore speculate that scavenging of hydrogen from the gold by the support acts to promote the above two reactions, but not the homocoupling of iodobenzene to produce biphenyl, in accord with observation.…”
mentioning
confidence: 71%
“…[16] In particular, Pd/CeO 2 catalysts are largely used in a variety of dehydrogenation and oxidation reactions. [17][18][19][20][21][22][23][24][25][26] One of the key functions of this material is the ability of Ce to switch between the Ce 4 + and Ce 3 + oxidation states, which allows the reversible addition and removal of oxygen, the socalled oxygen storage capacity (OSC). Previous studies have shown that the addition of CeO 2 to Pd/Al 2 O 3 promotes the oxidation of Pd.…”
Section: Introductionmentioning
confidence: 99%
“…The esters were hydrogenated and compared with the initial products [12,13]. After hydrogenation of the double bonds in the ring, the TOS of esters XVII-XIX improved to some degree [14].…”
mentioning
confidence: 99%